Assessing the municipal service quality of residential neighborhoods based on SERVQUAL, AHP and Citizen's Score Card: A case study of Dhaka North City Corporation area, Bangladesh - Sadia Afroj; Fahmida Hanif; Muntasir Bin Hossain; Nafis Fuad; Ishrat Islam; Nusrat Sharmin; Fariba Siddiq (Journal of Urban Management, 2021)
Rapid urban population growth stimulates the challenges of city government authorities in providing the municipal services adequately considering the citizen's demand. While the gap persists between the service provision and citizen's perception on it, the quality of life of cities may deteriorate due to psychological dissatisfaction of dwellers with urban services. Hence the evaluation of the urban service quality from the citizen's perspective and accordingly addressing the gap is necessary for sustainable urban management. This study shows a common framework incorporating SERVQUAL, Analytical Hierarchy Process (AHP) and Citizen's Score Card to define the quality of municipal services spatially and functionally based on the satisfaction of citizens. The items under the dimensions of SERVQUAL and the weightages of each dimension were set through literature review and expert opinion. Dhaka, the only megacity of Bangladesh is experiencing an impetuous growth towards its northern portion and Dhaka North City Corporation (DNCC) is the responsible authority to supply the municipal facilities within this area. Nine residential neighborhoods having homogeneous characteristics in terms of population density, residential land use, built up area and income level within the jurisdictional area of DNCC were selected to collect the data. The data were collected through household questionnaire survey using stratified random sampling technique where people responded for each SERVQUAL questions and scored the facilities provided by the DNCC. The result shows citizens are moderately satisfied (63.3%) with municipal services aggregately. To meet the demand of dwellers, the city government authority should be more functional, reliable and participatory and be equipped with qualified manpower and facilities. Despite the locational characteristics are uniform among the case areas, Ward 3, Ward 4 and Ward 31 are in unprivileged state in terms of municipal services. The facilities of public toilet, parking and disaster management activities performed by DNCC are commonly in unsatisfactory state in all areas that require special attention from the authority. Based on the findings, it could be stated that where the city government authority is roughly unsusceptible to meet the demand of the existing population, the enormous population growth within urban areas could affect the life quality poorly. Therefore this paper would fetch a course where the deficiency on urban services would be evaluated under a common arena considering the psychological aspect of citizen, thereby priority interventions could be ascertained for enhancing the life quality of urban areas.
Keywords: 710; Municipal service; SERVQUAL; AHP; Score card; DNCC; Citizen’ s satisfaction